Governance Strategy Juridical Rural Creative Economy Respond To Competitive Global Competition - Adnyani, Ni Ketut Sari; Sudiatmaka, Ketut; Landrawan, I Wayan (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2022)
This research is motivated because of the importance of legal protection also serves as protection for the governance of the rural economy, among others, can we review the various forms of business startups together or independent creative such as from several sectors among others include: crafts produced by businesses traditional craft "weaving" typical Bali, whether generated by an individual or collective basis. Activities of corporate governance in achieving the goal must always be done with the provisions of applicable law. In case this is not rare in the field that many business activities that have not been able to carry out the legal relationship for the corporate governance businesses without first consulting with legal teams, and business people never know when the legal relationship occurs. The lack of knowledge and understanding of the technical legal advice resulted in the governance of rural creative economy also occur in governance typical handicraft industry Endek Klungkung be difficult to develop and the potential of the craft. Methodologically, this study is the development of research in the engineering building public policy on rural economic governance creative competitive in the face of global competition. This research, that research is a digger / primary data collection tool. Research, difficulties for businesses in the countryside in conducting the governance of creative economic development, that despite constraints in the production, management, marketing, collaboration and licensing are also difficulties in connection with public knowledge of related legal actions that could be proved from the people who do not know procedures and in the management of copyright as a form of lack of legal awareness of the local community. Strategy juridical taken by the manager of the creative economy is rustic in to protect against the type of business and deliver services to consumers, the community's knowledge related to legal remedies that can be done to protect the product of the creative economy to rural areas of action flagiasi and coordinate with Disperindag related to administrative registration of copyright which are owned.